Correlation analysis of tensile strength and chemical composition of basalt fiber roving. Issue 7 (13th December 2018) - Ding, Lining; Liu, Ying; Liu, Jianxun; Wang, Xin
Abstract : This article studies the correlation between the tensile strength and the chemical composition of basalt fiber roving and analyzes rovings with different chemical compositions to derive equations that predict the roving strength. The tensile properties of different types of basalt fiber roving that were impregnated with two types of resins were first tested, while the chemical compositions of the basalt fibers were analyzed. The functional roles played by different chemical constituents and their contributions to the tensile strength were analyzed and used to verify the correlation between the strength and the effective composition. A numerical method was used to derive equations to predict the strength of the basalt fibers. The results show that the tensile strengths of the impregnated basalt fiber roving vary from 2313 to 2714 MPa, depending on the manufacturers, and were 7–25% higher than that of E‐glass fiber roving. The chemical constituents of the basalt fibers play four different functional roles, network formers, network intermediates, network changers and network modifiers. Chemical composition groups are subsequently identified that have positive, negative and uncertain effects on the tensile strength. The weighting factors of the chemical composition are regressed, resulting in predictions for the tensile strength that are in good agreement with experimental measurements. The results from this study can be used to predict the strength of basalt fibers in basalt mineral analysis. POLYM. COMPOS., 40:2959–2966, 2019. © 2018 Society of Plastics Engineers